THE SUBSTRATE OF REALITY IN THE MYTH OF THE GREAT HERO YU (in the context of sources from ancient chinese literature) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this report, we continue to acquaint you with the main variants of the myth of the flood recorded in the most ancient literary monuments of China. Stories about the flood from ancient Chinese mythology have always been popular among the people. This fact contributed to both their preservation and re-registration. In the first report, “The Flood, Mythology and Gun”, we told about the struggle, suffering and tragedy of the cultural hero Gun in curbing a natural disaster in the Celestial Empire. In this report, we focused on the victory of Yu, the son of Gun, in the fight against the same natural disasters.
Keywords: myth, reality, source, reflection, image, cultural hero, research, idealization, character.